Immunotherapy targeting glicolipid antigen (GD2) expressed on neuroblastoma tumour cells. Review of literature - Gawin, Konrad; Ignasiak, Anita; Zawiślak, Wiktoria; Rychlica, Kacper; Cisowski, Michał; Dąbrowska, Maria; Cholewińska-Rychlica , Jolanta; Madura, Paulina; Mrozik-Gałecka, Daria (Quality in Sport, 2026)
Neuroblastoma is the most common extracranial solid tumor of childhood and accounts for approximately 15% of pediatric cancer-related mortality. Despite advances in multimodal therapy, outcomes for patients with high-risk disease remain unsatisfactory, with long-term survival rates below 50%. Disialoganglioside GD2, highly expressed on neuroblastoma cells, has become a key therapeutic target enabling the development of monoclonal antibodies such as dinutuximab beta and naxitamab. Anti-GD2 antibodies exert antitumor activity through complement activation, antibody-dependent cellular cytotoxicity, and antibody-dependent phagocytosis, mechanisms that can be further enhanced by cytokines including IL-2 and GM-CSF. Clinical studies demonstrate that immunotherapy incorporating anti-GD2 antibodies significantly improves event-free and overall survival compared with standard isotretinoin maintenance, although treatment is frequently limited by severe neuropathic pain and other adverse reactions. Recent findings highlight the potential of copper chelation as an adjuvant strategy. Additionally, naxitamab-based chemoimmunotherapy shows promising activity in patients with refractory or minimal residual disease. This review summarizes the current landscape of GD2-directed immunotherapy, supportive approaches such as ketamine-based analgesia, and emerging synergistic strategies, including copper chelation, that may further optimize therapeutic outcomes in high-risk neuroblastoma.